Enzyme-Linked Immunoassay-Based Quantitative Measurement of Apolipoprotein B (ApoB) in Dried Blood Spots, a Biomarker of Cardiovascular Disease Risk. (3rd April 2017) - Eick, Geeta N.; Kowal, Paul; Barrett, Tyler; Thiele, Elizabeth A.; Snodgrass, J. Josh
ABSTRACT: Apolipoprotein B (ApoB) is a strong predictor of cardiovascular disease, which remains the leading cause of mortality in both higher and lower income countries. Here, we adapted an enzyme-linked immunosorbent assay (ELISA) development kit for quantitative determination of ApoB levels in serum and plasma for use with dried blood spots (DBS). After confirming the dilution linearity of the assay for DBS, we measured ApoB in 208 venous DBS samples. Then, using Passing-Bablok regression analysis and Spearman rank correlation analysis, we evaluated the correspondence in ApoB values between matched plasma and finger-prick DBS samples from 40 individuals who had ApoB values spanning the range of ApoB values observed in the 208 vDBS samples. We also evaluated assay precision and recovery, the effects of hematocrit, number of freeze-thaw cycles, and different storage temperatures on ApoB levels in DBS. There was a strong, significant correlation between plasma and DBS ApoB levels with little bias. Assay precision and recovery were within the range recommended by the U.S. government's industry guidelines for bioanalytical assay validation. The assay was not affected by the DBS matrix or physiological hematocrit levels. This DBS-based ELISA assay will facilitate population-scale assessment of cardiovascular risk in previously unexplored populations.